Preparation method of porous alumina refractory material reinforced by Alq3 regulated alumina whisker
Patent Information
- Application Number
- CN202611325038.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]针对现有技术的不足,本发明的目的在于提供一种Alq3调控烧结收缩的氧化铝晶须增强耐高温碱蒸气多孔氧化铝耐火材料,旨在解决多孔氧化铝耐火材料高温烧结收缩显著、制品易产生裂纹缺陷;高温碱蒸气易侵入基体造成材料腐蚀失效,且常规配方难以协同实现低收缩、高韧性与优异抗碱侵蚀性能的技术问题
1.本发明引入Alq3作为调控烧结收缩的功能助剂。该助剂在低温烧结中,于氧化铝颗粒间隙生成大量弥散分布的亚微米级微小空隙,有效增大颗粒初始间距,延缓颗粒相互接触及烧结颈的形成,降低耐火材料烧结收缩。
Smart Images

Figure CN122897668A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of refractory material preparation and application technology, specifically to a high-temperature alkali vapor resistant porous alumina refractory material with Alq3-controlled sintering shrinkage and alumina whisker reinforcement. Background Technology
[0002] Alumina-based refractories possess excellent properties such as high temperature resistance, corrosion resistance, long service life, and recyclability, making them one of the core lining materials commonly used in industrial high-temperature kilns, with enormous potential for engineering applications. Currently, however, these refractories still suffer from significant structural defects and performance shortcomings during sintering and high-temperature service. One major bottleneck in their development is the poor controllability of volume shrinkage during sintering. During sintering, the alumina matrix undergoes particle rearrangement, grain boundary migration, and pore collapse, resulting in significant volume shrinkage, which can easily cause product cracking and dimensional deviations. Disordered shrinkage can also damage the matrix's pore structure, leading to large pore sizes and uneven pore distribution. Simultaneously, uneven shrinkage induces internal residual stress, promoting the generation and propagation of microcracks, reducing material strength, and limiting their use in high-precision, long-life, high-temperature applications. During high-temperature service, the raw materials processed within the kiln contain certain alkali metal components. Under high-temperature conditions, these readily volatilize to form alkaline vapors, and the refractory material, as a lining, will be continuously exposed to these gases. It can penetrate into the matrix along the pores of the refractory material, causing a chemical reaction and a volume expansion effect, leading to material loosening, delamination, and structural failure, which will severely shorten the service life of the kiln lining. Therefore, developing porous alumina refractory materials with both low sintering shrinkage and high resistance to alkali vapor permeation is of practical significance for improving the reliability of linings under such harsh conditions.
[0003] A patented technology for a refractory material for the interior of a rotary kiln (CN202211323049.1) discloses a composite refractory material prepared by chemical grafting. The shortcomings of this refractory material are: 1) the amidation reaction at high temperatures is complex and uncontrollable; 2) the reaction produces polluting gases. A patented technology for a composite castable, preparation method, and application for pulverized coal injection pipes in cement kilns (CN202511279742.7) involves adding ZrO2. TiO2 The effect of Al2O3 precursor powder in preventing sample cracking through in-situ reaction at 1100~1300℃ to generate micro-expansion is limited and it introduces other impurities. A patent (CN202110516946.3) discloses a method for preparing an aluminum-silicon castable with low sintering shrinkage using perlite as aggregate and the introduction of capacitor ceramsite sand as an aid. However, the interface bonding between the capacitor ceramsite sand and the matrix is poor, resulting in weak material mechanical properties. A patent (CN201210123564.5) discloses a method for preparing lightweight magnesium-aluminum spinel thermal insulation material, utilizing volume expansion during spinelization to solve the cracking problem caused by uneven sintering shrinkage. However, its drawbacks include: 1) a large amount of water is added during the process, resulting in a long material drying time and low production efficiency; 2) the crosslinking agents and catalysts introduced in the process can produce harmful substances at high temperatures.
[0004] This patent utilizes Alq3, a novel multifunctional sintering regulator capable of precisely controlling the sintering shrinkage of alumina-based refractories. This substance exhibits gradient pyrolysis characteristics: at low temperatures, organic ligands gradually decompose and volatilize, forming uniform micropores within the green body, reserving sintering buffer space to offset matrix densification shrinkage and prevent product deformation and pore collapse; at high temperatures, highly active nano-alumina particles are generated in situ, coating the surface of matrix particles, inhibiting abnormal grain growth, and the accompanying volume expansion further compensates for sintering shrinkage. The optimized microstructure resulting from Alq3's gradient pyrolysis regulation reduces alkali vapor permeation channels at the material's structural level, inhibiting alkali vapor intrusion into the matrix and significantly improving the material's high-temperature resistance to alkali vapor corrosion. Furthermore, Alq3 exhibits excellent compatibility and good interfacial bonding with the alumina matrix, providing a new approach for preparing dimensionally stable alumina-based refractories with high resistance to alkali vapor corrosion. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide an Alq3-controlled sintering shrinkage-reinforced porous alumina refractory material with alumina whiskers and high-temperature alkali vapor resistance. This invention aims to solve the technical problems of significant high-temperature sintering shrinkage of porous alumina refractory materials, easy cracking defects in the products, easy penetration of high-temperature alkali vapor into the matrix causing material corrosion failure, and the difficulty of achieving low shrinkage, high toughness and excellent alkali corrosion resistance through conventional formulations.
[0006] This porous alumina refractory material uses two types of alumina micropowder with different particle sizes as the main raw materials, selects starch as a pore-forming agent and curing agent, introduces rare earth oxides La2O3 and Eu2O3 as sintering aids, and adds alumina whiskers as a reinforcing phase. The key ingredient is aluminum tris(8-hydroxyquinoline) alloy (Alq3), which is introduced as a core anti-sintering shrinkage functional aid. It is prepared using a starch consolidation molding process combined with solid-phase reaction sintering. Alq3 is the core component of this invention for improving sintering shrinkage defects, possessing unique and excellent high-temperature controllable expansion characteristics. It can produce uniform and moderate volume expansion throughout the low-temperature sintering and high-temperature sintering processes, accurately compensating for and offsetting the inherent volume shrinkage of the alumina matrix during sintering, inhibiting defects such as cracks and interconnected pores caused by shrinkage stress within the matrix, improving the forming accuracy and high-temperature structural stability of the product, and thus inhibiting the intrusion of alkali vapor into the matrix from the material structure. In addition, the network structure formed by the overlapping of alumina whiskers effectively inhibits the diffusion of alkali vapor into the interior; at the same time, during the alkali erosion process, the expansion of cracks in the refractory material is effectively inhibited through mechanisms such as pull-out and fracture, thereby improving the alkali erosion resistance of the refractory material.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a high-temperature alkali vapor resistant porous alumina refractory material with tris(8-hydroxyquinoline)alumina (Alq3) controlled sintering shrinkage reinforced by alumina whiskers includes the following steps: (1) Alq3 low temperature activation pretreatment: Tris(8-hydroxyquinoline) aluminum (Alq3) powder was placed in a vacuum drying oven for gradient low temperature activation treatment, then heated and dried at a constant temperature to remove trace adsorbed impurities, and then cooled naturally to avoid powder agglomeration. After gentle grinding and sieving, highly dispersed and highly active Alq3 powder was obtained. (2) The pretreated Alq3 powder, two kinds of α-alumina micro powders with different particle sizes, rare earth sintering aids La2O3 and Eu2O3, pore-forming agent starch and alumina whiskers are mixed evenly to obtain a mixture; (3) Add water to the mixture obtained in step (2) and mix evenly to obtain a slurry; (4) The slurry obtained in step (3) is poured into a green sample, cured and demolded, and then the sample is dried. (5) The sample dried in step (4) is subjected to high-temperature heat treatment and then cooled in the furnace to obtain an Alq3-controlled sintering shrinkage-reinforced high-temperature alkali vapor-resistant porous alumina refractory material with alumina whisker reinforcement.
[0008] In step (1), Alq3 powder is used to compensate for the shrinkage of the material during high-temperature sintering, and the particle size is 0.5 to 3 μm; based on the total mass of alumina micro powder being 100%, the amount of Alq3 added is 1 to 8%.
[0009] As described above, in step (1), the vacuum low-temperature activation temperature is 40-60 ℃ and the time is 1-3 h, and the high-temperature impurity removal temperature is 70-100 ℃ and the time is 4-7 h; In step (2), the alumina powder includes calcined α-alumina powder and active α-alumina powder (purchased from Hubei Siman New Materials Co., Ltd.).
[0010] The D50 of the calcined α-alumina micro powder is 5–10 μm, and the D50 of the active α-alumina micro powder is 1–4 μm.
[0011] The pore-forming agent is starch, specifically potato starch, with a D50 of 30–50 μm.
[0012] The sintering aids are La2O3 and Eu2O3.
[0013] In step (2), the amount of active α-alumina micro powder added is 15-30% based on a total mass of 100% alumina micro powder; The amount of starch added as a pore-forming agent is 6-15%; The amount of Eu2O3 added is 0.5-3%, and the mass ratio of La2O3 to Eu2O3 is 1:1-6; The amount of alumina whiskers added is 1-5%; The remainder is calcined α-alumina micro powder.
[0014] In step (2), the mixing speed is 140-160 r / min and the mixing time is 120-240 min. In step (3), the solid content of the slurry is 65-70 wt% and the stirring time is 30-60 min. In step (4), the curing temperature is 80-85℃ and the curing time is 120-180 min. The drying process involves drying at 60–80°C for 12–24 hours, followed by drying at 110–120°C for another 12–24 hours.
[0015] In step (5), the heating procedure for the high-temperature heat treatment is as follows: the temperature is increased from room temperature to 300-400℃ at a rate of 1-5℃ / min, and held for 1-2 hours; then the temperature is increased to 500-800℃ at a rate of 1-5℃ / min, and held for 2-3 hours; finally, the temperature is increased to 1400-1600℃ at a rate of 1-5℃ / min, and held for 3-5 hours.
[0016] This invention provides a high-temperature alkali vapor resistant porous alumina refractory material with Alq3-controlled sintering shrinkage reinforced by alumina whiskers, prepared by the above preparation method.
[0017] The present invention also provides the application of the above-mentioned Alq3-controlled sintering shrinkage-regulated alumina whisker-reinforced high-temperature alkaline vapor-resistant porous alumina refractory material in an alkaline atmosphere.
[0018] The performance parameters of the high-temperature alkali vapor resistant porous alumina refractory material with Alq3-controlled sintering shrinkage prepared by the above method are as follows: linear shrinkage rate before and after high-temperature sintering is 0.87–1.41%, and bulk density is 1.50–1.60 g / cm³. 3 The apparent porosity is 49.98–58.71%, the flexural strength is 13.10–28.78 MPa, and the thermal conductivity at room temperature is 1.9–3.6 W·m. -1 ·k -1 The preferred thermal conductivity at room temperature is 1.9–2.5 W·m. -1 ·K -1 In the alkaline vapor erosion test at 1300 ℃, no obvious erosion marks were found on the surface of the sample after 5 h of erosion, and the mass did not change significantly before and after erosion, indicating that it has good resistance to alkaline vapor erosion.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention introduces Alq3 as a functional additive to regulate sintering shrinkage. During low-temperature sintering, this additive generates a large number of dispersed submicron-sized micropores between alumina particles, effectively increasing the initial particle spacing, delaying particle contact and the formation of sintering necks, and reducing sintering shrinkage of refractory materials.
[0020] 2. This invention introduces Alq3 as a functional aid for regulating sintering shrinkage. After the organic framework decomposes during high-temperature sintering, Al atoms are transformed in situ into nano-alumina (initially as a γ / θ-Al2O3 transition phase). The evolution of the transition phase is accompanied by a volume effect, and the generated alumina is uniformly deposited on the surface of coarse α-Al2O3 particles, acting as a rigid isolation fulcrum to prevent the matrix alumina particles from contacting and fusing with each other, effectively reducing the high-temperature sintering shrinkage of the refractory material.
[0021] 3. In the alkali vapor-resistant alumina whisker-reinforced porous alumina refractory material prepared by this invention, Alq3 decomposes at high temperatures. This thermal decomposition process compensates for the volume shrinkage effect caused by sintering, effectively reducing the overall sintering shrinkage rate of the product and suppressing defects such as cracks and interconnected pores caused by shrinkage stress within the matrix. This achieves structural inhibition of alkali vapor intrusion into the matrix. Simultaneously, the whiskers, uniformly dispersed within the pores of the refractory material, interweave to form a complex, interwoven network structure, effectively controlling the pore size and hindering the penetration of alkali vapor into the matrix, significantly improving the material's resistance to alkali vapor corrosion. After 5 hours of alkali vapor corrosion at 1300℃, the mass increase rate of this refractory material is less than 1.3%, demonstrating excellent alkali corrosion resistance and suitability for alkaline operating environments. Attached Figure Description
[0022] Figure 1 The microstructure of the alumina whiskers used in Example 1 is shown.
[0023] Figure 2 The XRD patterns of the samples prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are shown.
[0024] Figure 3 Macroscopic images are shown of the samples prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 after alkaline vapor etching at 1300℃ for 5 h. The samples in the images, from bottom to top, are Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4. Detailed Implementation
[0025] The present invention will be further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0026] It should be noted that, unless otherwise specified, all chemical reagents involved in this invention were purchased through commercial channels.
[0027] Example 1 (1) 3.9 g of Alq3 powder was placed in a vacuum drying oven for low-temperature activation treatment at 60 ℃ for 2 h, and then heated to 80 ℃ for constant temperature drying for 6 h to remove trace adsorbed impurities. Finally, it was cooled naturally in the oven and sieved to obtain pretreated Alq3 powder.
[0028] (2) The pretreated Alq3 powder, chemically pure La2O3 and chemically pure Eu2O3 in a mass ratio of 1:4, 292.5 g of calcined α-alumina micro powder, 97.5 g of active α-alumina, 46.8 g of starch and 11.7 g of alumina whiskers were placed in a drum and mixed for 120 min at a speed of 150 r / min until the mixture was homogeneous and a mixture was obtained.
[0029] (3) Then add water to prepare a slurry with a solid content of 65%.
[0030] (4) The slurry obtained in step (3) is poured into a green sample, cured at 85 ℃ for 180 min and then demolded. The sample is then dried at 60 ℃ for 24 h and at 110 ℃ for 12 h.
[0031] (5) The dried sample from step (4) is subjected to high-temperature heat treatment. The heating program for high-temperature heat treatment is as follows: first, the temperature is increased from room temperature to 300 ℃ at a rate of 2 ℃ / min and held for 1 h; then, the temperature is increased to 500 ℃ at a rate of 2 ℃ / min and held for 2 h; finally, the temperature is increased to 1550 ℃ at a rate of 3 ℃ / min and held for 3 h. Then, the sample is cooled in the furnace to obtain an Alq3-controlled sintering shrinkage-reinforced alumina whisker-reinforced high-temperature alkali vapor-resistant porous alumina refractory material.
[0032] Figure 1 The image shows the morphology of the alumina whiskers used in Example 1. Observation reveals that the alumina whiskers exhibit a one-dimensional rod-like morphology, with complete crystallization and good dispersion. Figure 2 The XRD pattern for Example 1 shows that, due to the complete thermal decomposition and burn-off of the organometallic complex Alq3 during the heating process, the XRD pattern of the sintered body only detected the α-Al2O3 phase and the composite phase formed by the reaction of the alumina matrix and rare earth oxides; no characteristic diffraction peaks of Alq3 were observed. This indicates that Alq3 does not remain in the final sintered product, and its role in inhibiting high-temperature sintering shrinkage mainly occurs during the sintering heating stage: Alq3 gradually decomposes in the medium-high temperature range, which can buffer the densification sintering driving force between alumina particles, alleviate the strong volume shrinkage generated during the high-temperature sintering of the matrix, and ultimately obtain a low-shrinkage porous alumina refractory material.
[0033] Example 2 (1) 15.6 g of Alq3 powder was placed in a vacuum drying oven for low-temperature activation treatment at 40 °C for 1 h, and then heated to 70 °C for constant temperature drying for 7 h to remove trace adsorbed impurities; finally, it was cooled naturally in the oven and sieved to obtain pretreated Alq3 powder.
[0034] (2) The pretreated Alq3 powder, chemically pure La2O3 and chemically pure Eu2O3 in a mass ratio of 1:1, 331.5 g of calcined α-alumina micro powder, 58.5 g of active α-alumina, 35.1 g of starch and 3.9 g of alumina whiskers were placed in a drum and mixed for 160 min at a speed of 140 r / min until the mixture was uniform and a mixture was obtained.
[0035] (3) Then add water to prepare a slurry with a solid content of 68%.
[0036] (4) The slurry obtained in step (3) is poured into a green sample, cured at 80 ℃ for 140 min and then demolded. The sample is then dried at 60 ℃ for 12 h and at 115 ℃ for 24 h.
[0037] (5) The dried sample from step (4) is subjected to high-temperature heat treatment. The heating program for high-temperature heat treatment is as follows: first, the temperature is increased from room temperature to 400 ℃ at a rate of 1 ℃ / min and held for 1 h; then, the temperature is increased to 600 ℃ at a rate of 1 ℃ / min and held for 3 h; finally, the temperature is increased to 1500 ℃ at a rate of 5 ℃ / min and held for 4 h. Then, the sample is cooled in the furnace to obtain an Alq3-controlled sintering shrinkage-reinforced alumina whisker-reinforced high-temperature alkali vapor-resistant porous alumina refractory material.
[0038] Example 3 (1) 31.2 g of Alq3 powder was placed in a vacuum drying oven for low-temperature activation treatment at 50 °C for 3 h, and then heated to 100 °C for constant temperature drying for 4 h to remove trace adsorbed impurities; finally, it was cooled naturally in the oven and sieved to obtain pretreated Alq3 powder.
[0039] (2) The pretreated Alq3 powder, chemically pure La2O3 and chemically pure Eu2O3 in a mass ratio of 1:2, 312 g of calcined α-alumina micro powder, 78 g of active α-alumina, 23.4 g of starch and 19.5 g of alumina whiskers were placed in a drum and mixed for 240 min at a speed of 160 r / min until the mixture was homogeneous and a mixture was obtained.
[0040] (3) Then add water to prepare a slurry with a solid content of 70%.
[0041] (4) The slurry obtained in step (3) is poured into a green sample, cured at 83 °C for 160 min and then demolded. The sample is then dried at 70 °C for 16 h and at 120 °C for 20 h.
[0042] (5) The dried sample from step (4) is subjected to high-temperature heat treatment. The heating program for high-temperature heat treatment is as follows: first, the temperature is increased from room temperature to 400 ℃ at a rate of 3 ℃ / min and held for 2 h; then, the temperature is increased to 500 ℃ at a rate of 5 ℃ / min and held for 3 h; finally, the temperature is increased to 1600 ℃ at a rate of 1 ℃ / min and held for 3 h. Then, the sample is cooled in the furnace to obtain an Alq3-controlled sintering shrinkage-reinforced alumina whisker-reinforced high-temperature alkali vapor-resistant porous alumina refractory material.
[0043] Example 4 (1) 7.8 g of Alq3 powder was placed in a vacuum drying oven for low-temperature activation treatment at 50 °C for 2 h, and then heated to 90 °C for constant temperature drying for 5 h to remove trace adsorbed impurities; finally, it was cooled naturally in the oven and sieved to obtain pretreated Alq3 powder.
[0044] (2) The pretreated Alq3 powder, chemically pure La2O3 and chemically pure Eu2O3 in a mass ratio of 1:6, 273 g of calcined α-alumina micro powder, 117 g of active α-alumina, 58.5 g of starch and 3.9 g of alumina whiskers were placed in a drum and mixed for 180 min at a speed of 150 r / min to obtain a mixture.
[0045] (3) Then add water to prepare a slurry with a solid content of 65%.
[0046] (4) The slurry obtained in step (3) is poured into a green sample, cured at 85 ℃ for 120 min and then demolded. The sample is then dried at 80 ℃ for 24 h and at 110 ℃ for 15 h.
[0047] (5) The dried sample from step (4) is subjected to high-temperature heat treatment. The heating program for high-temperature heat treatment is as follows: first, the temperature is increased from room temperature to 300 ℃ at a rate of 5 ℃ / min and held for 2 h; then, the temperature is increased to 800 ℃ at a rate of 3 ℃ / min and held for 2 h; finally, the temperature is increased to 1400 ℃ at a rate of 2 ℃ / min and held for 5 h. Then, the sample is cooled in the furnace to obtain an Alq3-controlled sintering shrinkage-reinforced alumina whisker-reinforced high-temperature alkali vapor-resistant porous alumina refractory material.
[0048] Comparative Example 1 Same as Example 1, except that it does not contain alumina whiskers.
[0049] Comparative Example 2 Same as Example 1, except that in step (1), the activation is carried out at 80°C for 8 hours.
[0050] Comparative Example 3 Same as Example 1, except that the activation temperature of Alq3 is 30°C and the activation time is 8h.
[0051] Comparative Example 4 Same as Example 1, except that it does not contain step (1).
[0052] The alumina refractory materials prepared in Examples 1-4 and Comparative Examples 1-4 were made into samples for performance testing.
[0053] The external dimensions of the refractory material samples before and after sintering were measured using vernier calipers. Each group of samples underwent three dimensional measurements. The degree of shrinkage during the sintering process of the refractory material was characterized by the linear shrinkage rate.
[0054] The test results are shown in Table 1: Table 1: Linear shrinkage rate of refractory materials before and after sintering
[0055] The bending resistance of the specimen was tested using the three-point bending method. The equipment was an electronic universal testing machine (model UMT5105). The specimen size was 150 mm × 40 mm × 14 mm (length × width × height). The span during the test was 100 mm, and the loading rate was 0.5 mm / min.
[0056] The sample was placed in a high-temperature environment of 1300 ℃ and etched for 1 to 5 h by alkaline vapor generated by the high temperature heating of sodium carbonate (Na2CO3). After completion, the mass of the sample was measured and the mass growth rate was calculated to evaluate the resistance of porous alumina ceramics to alkaline atmosphere erosion.
[0057] The test results are shown in Table 2: Table 2: Mass growth rate of samples after 5 h of alkaline vapor etching at 1300 ℃
[0058] Figure 3 Macroscopic images are shown of samples prepared in Example 1 of the present invention, as well as Comparative Examples 1, 2, 3, and 4, after alkaline vapor etching at 1300°C for 5 h. In these images, the samples, from bottom to top, are Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4. Figure 3 It can be seen that after 5 hours of alkaline vapor etching treatment at 1300 ℃, no obvious corrosion marks were observed on the surface of Example 1, while obvious alkaline vapor etching marks were observed on the surfaces of Comparative Examples 1, 2, 3, and 4. This phenomenon arises from a synergistic effect of two factors: Firstly, Alq3 decomposes at high temperatures, and this decomposition process offsets the volume shrinkage during sintering, reducing the overall sintering shrinkage rate of the sample and decreasing defects such as cracks and interconnected pores caused by shrinkage within the matrix, thus structurally inhibiting the penetration of alkaline etching gases into the material. Secondly, the alumina whisker network structure formed within the system alters and prolongs the erosion diffusion path of alkaline vapor, hindering rapid mass transfer of alkaline vapor within the material. Under the synergistic effect of Alq3 and alumina whiskers, the alkaline vapor erosion resistance of the Example 1 sample is improved, while the comparative samples lacking this synergistic structure cannot effectively block alkaline vapor intrusion, thus exhibiting obvious erosion damage characteristics on their surfaces.
[0059] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for preparing Alq3-regulated alumina whisker-reinforced porous alumina refractory material, characterized in that, Includes the following steps: (1) Tris(8-hydroxyquinoline) aluminum (Alq3) powder was subjected to vacuum low-temperature activation pretreatment to obtain highly dispersed and highly active Alq3 powder; (2) Mix the Alq3 powder, alumina micro powder, pore-forming agent, sintering aid and alumina whiskers after step (1) evenly to obtain a mixture; (3) Add water to the mixture obtained in step (2) and mix evenly to obtain a slurry; (4) The slurry obtained in step (3) is poured into a mold, cured and demolded, and then dried to obtain a green sample; (5) The green sample obtained in step (4) is subjected to high-temperature heat treatment and then cooled in the furnace to obtain the porous alumina refractory material.
2. The preparation method according to claim 1, characterized in that: In step (1), the Alq3 powder is used to compensate for the shrinkage of the material during high-temperature sintering, and the particle size is 0.5 to 3 μm; based on the total mass of alumina micro powder being 100%, the amount of Alq3 added is 1 to 8%.
3. The preparation method according to claim 1, characterized in that: In step (1), the vacuum low-temperature activation temperature is 40-60℃ and the activation time is 1-3h; then the temperature is raised to 70-100℃ and dried at a constant temperature for 4-7h to remove trace adsorbed impurities; after natural cooling, it is ground and sieved.
4. The preparation method according to claim 1, characterized in that: In step (2), the alumina micro powder includes calcined α-alumina micro powder and active α-alumina micro powder; The D50 of the calcined α-alumina micro powder is 5-10 μm, and the D50 of the active α-alumina micro powder is 1-4 μm; The pore-forming agent is starch, specifically potato starch, with a D50 of 30–50 μm. The sintering aids are La2O3 and Eu2O3.
5. The preparation method according to claim 1, characterized in that: In step (2), based on a total mass of alumina micro powder of 100%, The amount of active α-alumina micro powder added is 15-30%; The amount of starch added as a pore-forming agent is 6-15%; The amount of Eu2O3 added is 0.5-3%, and the mass ratio of La2O3 to Eu2O3 is 1:1-6; The amount of alumina whiskers added is 1-5%; The remainder is calcined α-alumina micro powder.
6. The preparation method according to claim 1, characterized in that: In step (2), the mixing speed is 140-160 r / min and the mixing time is 120-240 min; In step (3), the solid content of the slurry is 65-70 wt%; the stirring time is 30-60 min; In step (4), the curing temperature is 80-85℃ and the curing time is 120-180 min; The drying process involves drying at 60–80°C for 12–24 hours, followed by drying at 110–120°C for another 12–24 hours.
7. The preparation method according to claim 1, characterized in that: In step (5), the heating procedure for the high-temperature heat treatment is as follows: the temperature is increased from room temperature to 300-400℃ at a rate of 1-5℃ / min and held for 1-2 hours; then the temperature is increased to 500-800℃ at a rate of 1-5℃ / min and held for 2-3 hours; finally, the temperature is increased to 1400-1600℃ at a rate of 1-5℃ / min and held for 3-5 hours.
8. An Alq3-regulated alumina whisker-reinforced porous alumina refractory material prepared by the preparation method according to any one of claims 1 to 7, wherein the refractory material has a linear shrinkage rate of 0.87–1.41% before and after high-temperature sintering and a bulk density of 1.50–1.60 g / cm³. 3 The apparent porosity is 49.98–58.71%, the flexural strength is 13.10–28.78 MPa, and the thermal conductivity at room temperature is 1.9–3.6 W·m. -1 ·K -1 The preferred thermal conductivity at room temperature is 1.9–2.5 W·m. -1 ·K -1 .
9. The porous alumina refractory material according to claim 8, characterized in that: The refractory material undergoes a mass increase of less than 1.3% after being eroded by alkaline steam at 1300℃ for 1–5 hours.
10. The application of the porous alumina refractory material according to any one of claims 8 to 9 in a high-temperature alkaline atmosphere at 1300 to 1400°C.
Citation Information
Patent Citations
Method for manufacturing light magnesia-alumina spinel insulation materials
CN102659398B
Aluminum-silicon castable prepared by adjusting aggregate ratio and preparation method of aluminum-silicon castable
CN113185311A
A refractory material for the interior of a rotary kiln
CN115368153B
Composite castable for cement kiln coal injection duct, preparation method and application
CN121181342A